2018
DOI: 10.1002/art.40408
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation of CYP2E1 and DUSP22 Promoters Associated With Disease Activity and Erosive Disease Among Rheumatoid Arthritis Patients

Abstract: ObjectiveEpigenetic modifications have previously been associated with rheumatoid arthritis (RA). In this study, we aimed to determine whether differential DNA methylation in peripheral blood cell subpopulations is associated with any of 4 clinical outcomes among RA patients.MethodsPeripheral blood samples were obtained from 63 patients in the University of California, San Francisco RA cohort (all satisfied the American College of Rheumatology classification criteria; 57 were seropositive for rheumatoid factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 53 publications
3
26
0
Order By: Relevance
“…However, the finding of a robust and consistent correlation between methylation and DAS28 in those peripheral blood monocytes is of great value since it constitutes a less invasive approach to obtain biological samples from patients with RA. A previous study revealed that the hypomethylation of the CYP2E1 promoter in monocytes of patients with RA correlated to RA activity 23. By analysing our own data, we were also able to detect hypomethylation of the CYP2E1 promoter region.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, the finding of a robust and consistent correlation between methylation and DAS28 in those peripheral blood monocytes is of great value since it constitutes a less invasive approach to obtain biological samples from patients with RA. A previous study revealed that the hypomethylation of the CYP2E1 promoter in monocytes of patients with RA correlated to RA activity 23. By analysing our own data, we were also able to detect hypomethylation of the CYP2E1 promoter region.…”
Section: Discussionsupporting
confidence: 62%
“…Interestingly, the methylation profiles of both hypo.HA and hyper.HA CpG sites were highly similar between remission patients and healthy controls in an unsupervised representation (figure 2B and online supplementary figure 2C). We also inspected a DNA methylation dataset of monocytes of a cohort of patients with RA from a previously published study 23. By comparing their data and ours, we observed the same trend of changes in the methylomes in connexion with disease activity (see online supplementary figure 2D), despite that the patients with RA from Mok et al were classified using a different marker of disease activity, Clinical Disease Activity Index (CDAI).…”
Section: Resultssupporting
confidence: 54%
“…The involvement of DUSP22 as a negative regulator for the development of autoimmunity and Alzheimer's disease has been reported . Recently, the positive engagement of DUSP22 in the erosive disease among rheumatoid arthritis (RA) was suggested . Hypomethylation, observed among RA patients with erosive disease, leads to increased mRNA expression of DUSP22 , implying that DUSP22 could be involved in RA.…”
Section: Resultsmentioning
confidence: 99%
“…AZU1, LTBR, and RTEL1 are hypomethylated and involved in the autoimmune signaling cascade, indicating potential roles as epigenetic susceptibility markers (Wang et al, 2018). Hypomethylation of CYP2E1 is associated with disease activity and can be used as a disease activity marker (Mok et al, 2018). CD1C, TNFSF10, C6ORF10, and UBASH3A have the potential to be used as RA risk markers (Julia et al, 2017;Anaparti et al, 2019;Guderud et al, 2020).…”
Section: Dna Methylation As a Biomarker For Rheumatoid Arthritis Diagmentioning
confidence: 99%